Experiments with Buddhist Forms of Thought, Action and Practice to Promote Significant Learning - Regan, Julie (Religions, 2021)
While scholars have considered the centrality of teaching in Buddhist traditions and the rich pedagogical resources Buddhism has to offer academic courses on the topic, less attention has been paid to the ways in which Buddhist pedagogy might be applied to the overall structure of course design. This article addresses the challenges of presenting the richness and complexity of Buddhist traditions while also encouraging students to experientially engage such traditions in ways that promote transformative learning. It proposes using Buddhist pedagogical principles, together with a model of significant learning (Fink 2013), to design a course according to the Three Trainings in Wisdom, Ethics and Meditation. Framing the course as a series of experiments in Buddhist forms of thought, action, and practice highlights the critical perspective common to both Buddhist and academic approaches and helps maintain important distinctions between Buddhist traditions and popular secular practices. This article describes specific experiments with Buddhist ways of reading and analyzing classic and contemporary texts, films and images, together with experiments in Buddhist methods of contemplative and ethical practice, in an introductory course in order to help students see how forms of suffering that concern them might arise and be stopped or prevented from a Buddhist point of view.